1) Mg - MgO - Mg(OH)2 - MgSO4 - MgCl2 - Mg(NO3)2
2Mg + O2 = 2MgO
2NaOH + MgO = Mg(OH)2 + Na2O
Mg(OH)2 + H2SO4 = MgSO4 + 2H2O
MgSO4 + 2HCl = H2SO4 + MgCl2
MgCl2 + 2HNO3 = Mg(NO3)2 + 2HCl
2) S - SO2 - SO3 - H2SO4 - Na2SO4 - BaSO4
S + O2 = SO2
2SO2 + O2 = 2SO3
SO3 + H2O = H2SO4
2Na + H2SO4 = Na2SO4 + H2
Ba + Na2SO4 = BaSO4 + 2Na
3) Be - BeO - BeCl2 - Be(OH)2 - K2BeO2
2Be + O2 = 2BeO
BeO + 2HCl = BeCl2 + H2O
BeCl2 + 2NaOH = Be(OH)2 + 2HCl
Be(OH)2 + K2O = K2BeO2 + H2O
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1) Mg - MgO - Mg(OH)2 - MgSO4 - MgCl2 - Mg(NO3)2
2Mg + O2 = 2MgO
2NaOH + MgO = Mg(OH)2 + Na2O
Mg(OH)2 + H2SO4 = MgSO4 + 2H2O
MgSO4 + 2HCl = H2SO4 + MgCl2
MgCl2 + 2HNO3 = Mg(NO3)2 + 2HCl
2) S - SO2 - SO3 - H2SO4 - Na2SO4 - BaSO4
S + O2 = SO2
2SO2 + O2 = 2SO3
SO3 + H2O = H2SO4
2Na + H2SO4 = Na2SO4 + H2
Ba + Na2SO4 = BaSO4 + 2Na
3) Be - BeO - BeCl2 - Be(OH)2 - K2BeO2
2Be + O2 = 2BeO
BeO + 2HCl = BeCl2 + H2O
BeCl2 + 2NaOH = Be(OH)2 + 2HCl
Be(OH)2 + K2O = K2BeO2 + H2O